Proses Produksi Konten Promosi Feed Instagram oleh Divisi Creative Marketing di @halaman.omah - Silalahi, Ivani Valerine; Suparman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Instagram has become a major platform in digital marketing strategies, particularly for Food and Beverage (F&B) businesses in building brand awareness and audience engagement. This study aims to understand the production process of promotional content for Instagram feeds carried out by the Creative Marketing Division of @halaman.omah, as well as to identify the outcomes and challenges encountered during its implementation. This research employs a descriptive qualitative method through participatory observation during the Internship Program (PKL), interviews with one key informant, namely the Head of Creative Marketing, and literature review. The content production process consists of three main stages, namely pre-production, production, and post-production. Instagram analytics data show an 85% increase in views (from 33,415 to 61,824) with a consistently high percentage of non-follower audiences, indicating an improvement in engagement and brand awareness.